2017
DOI: 10.1097/icl.0000000000000260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cornea and Anterior Chamber Morphologic Changes After Penetrating Keratoplasty in Patients With Keratoconus

Abstract: Anterior chamber depth decreased significantly, but no change was observed in iridocorneal angle after penetrating keratoplasty in patients with keratoconus. Also, a decrease in the keratometric values and an increase in corneal thickness were observed. Understanding, estimating, and managing changes in the anterior chamber after penetrating keratoplasty, which induces significant changes in anterior chamber morphology, might increase the success of surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…However, there should not have been big differences in tomographic data between the groups just after PK. For example, KC eyes tend to have deeper ACD, but postoperative normalization of ACD by PK has been reported 19 , 20 . Also, inferior graft thinning, which was observed only in KC group, should not have existed at the time of PK.…”
Section: Discussionmentioning
confidence: 99%
“…However, there should not have been big differences in tomographic data between the groups just after PK. For example, KC eyes tend to have deeper ACD, but postoperative normalization of ACD by PK has been reported 19 , 20 . Also, inferior graft thinning, which was observed only in KC group, should not have existed at the time of PK.…”
Section: Discussionmentioning
confidence: 99%
“…ACD and keratometry values were reported to decrease signi cantly after PK due to tightened sutures, which straightened the cornea, and this effect increases with increased suture tension. 5 Onuchi et al…”
Section: Discussionmentioning
confidence: 99%
“…4 Both lamellar and penetrating keratoplasty procedures, which replace part of the recipient's corneal tissue with donor corneal tissue, may lead to signi cant anatomical changes to the cornea and anterior chamber structures. 5 Changes in the corneal thickness and curvature after corneal transplantation where corneal morphology is altered have an impact on IOP measurements. Lamellar techniques such as DALK and DMEK, which have additional stromal tissue and an interface between host and graft tissue, may have a different signi cance on IOP measurements in terms of corneal parameters.…”
mentioning
confidence: 99%
“…Although the trend of MSC change was obvious in the merged statistical analysis, comparisons among different keratoplasty types showed that PK led to more obvious morphological alterations compared with DALK on the first day after surgery. It was proved that the replacement of lamellar thickness of the corneal tissue of recipients causes less traction power to the corneoscleral tissue and anatomical changes to the anterior chamber angle when compared with full-thickness corneal tissue transplantation ( Ort et al, 2017 ). DALK preserves the intact Descemet’s membrane (DM) and endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…With an incidence rate of 5.5–31%, ocular hypertension (OHT) or secondary glaucoma (SG) in the early postoperative period after penetrating keratoplasty (PK) may lead to endothelial dysfunction and graft failure ( Karadag et al, 2010 ; Ali et al, 2011 ; Kornmann and Gedde, 2016 ). Changes of anterior chamber parameters, including anterior chamber depth and volume and iridocorneal angle, were detected after keratoplasty ( Gatzioufas et al, 2012 ; Ort et al, 2017 ), yet the SC was not explored. Therefore, we hypothesized that keratoplasty-induced anterior chamber structural changes, especially in the morphology of SC, could cause early postoperative OHT.…”
Section: Introductionmentioning
confidence: 99%